Italian Nostalgia: National and Global Identities of the Italian Novel - Anna Sofia Lippolis (Journal of Cultural Analytics)
The production, distribution and consumption of the Italian novel in the global editorial market has accompanied the gradual creation of a national branding process that does not coincide with the literary identity Italy tends to associate with. When considering the main analysis approaches of the Italian literary canon—the top-down one of the country’s yearly national bestsellers, literary prizes, suggested readings in Literature courses at University and school anthologies—and the larger-scale, bottom-up view of digital platforms like Amazon and Goodreads, Wikipedia stands in a middle, unexplored ground between the two. Through the comparative quantitative analysis of data derived from some of these sources, this article aims to gain more awareness on Italian literature from 1980 to 2021, to start addressing why national book prizes winners do not make it to the global market and if it is possible to talk about a national cultural resistance, which allowed authors like Elena Ferrante and Goliarda Sapienza to become literary sensations abroad before it happening in their own country. While some studies have already dealt with the unchanging aspect and the lack of diversity of the Italian literary canon, there has been little quantitative research on the two brands of the country, the national and the global, and on the dynamics between them. As well as proposing a methodology for the ongoing study of literary reception of Italian novels under multiple points of view, this article contributes to the discussion on the reliability of measures for studying the canon.